Prevalence and correlates of serostatus disclosure in HIV-infected adults attending the follow up and treatment clinic in Barbados. - Alok Kumar; Krishna R. Kilaru; Sheila Forde; Geeta Kumari (Social Medicine Publication Group, 2007)
Objective: To determine the extent of disclosure and factors associated with disclosure of HIV status to sexual partners, we interviewed HIV infected adults attending the centralized HIV clinics seeking medical care for HIV. Methods: The subjects were patients who attended the LRU for primary care and treatment of their HIV infection during the three months period of this study enrolment. Patients were asked to participate in this study after initial clinical care was performed, in a 30-minute standardized interview concerning behavioral, medical, and social history. Results: The study patients had the following characteristics: female, 42.7%; male, 57.3%; singles, 84.5%; married, 11.8%. The median age of respondents was 35 years, and 66.4% were employed. Seventy nine percent were sexually active, and of these 72% had a steady sex partner and 61% had one or more casual partners. Over all 64 (58.2%) of those interviewed, had disclosed their HIV status to significant others. Of the sixty three persons who had a steady partner 71.4% had self disclosed their HIV status to one or more steady partners. Of the fifty three persons who had one or more casual partners, 26.4% had self-disclosed their status to one or more casual partners. The most common reasons listed for nondisclosure to spouse or significant other were stigma/discrimination, fear of spread of information, rejection. Conclusion: Our findings suggest that both the knowing and unknowing sexual partners of HIV-infected persons continue to be at risk for HIV transmission.